2015
DOI: 10.14238/pi55.2.2015.65-69
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin for detecting community-acquired bacterial pneumonia

Abstract: Background Pneumonia is a major cause of morbidity and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This result was similar to a study by Bekdas M, et al 16 8 . Another study showed that the 0.5 ng/ml procalcitonin cut-off point had a sensitivity of 93% and a specificity of 74% as a marker of infection 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to a study by Bekdas M, et al 16 8 . Another study showed that the 0.5 ng/ml procalcitonin cut-off point had a sensitivity of 93% and a specificity of 74% as a marker of infection 17 .…”
Section: Discussionmentioning
confidence: 99%